A Novel TLR4-Binding Domain of Peroxiredoxin From Entamoeba histolytica Triggers NLRP3 Inflammasome Activation in Macrophages - Li, Xia; Feng, Meng; Zhao, Yanqing; Zhang, Yuhan; Zhou, Ruixue; Zhou, Hang; Pang, Zhen; Tachibana, Hiroshi; Cheng, Xunjia (Frontiers in Immunology, 2021)
Macrophages promote early host responses to infection by releasing pro-inflammatory cytokines, and they are crucial to combat amoebiasis, a disease affecting millions of people worldwide. Macrophages elicit pro-inflammatory responses following direct cell/cell interaction of Entamoeba histolytica, inducing NLRP3 inflammasome activation with high-output IL-1β/IL-18 secretion. Here, we found that trophozoites could upregulate peroxiredoxins (Prx) expression and abundantly secrete Prxs when encountering host cells. The C-terminal of Prx was identified as the key functional domain in promoting NLRP3 inflammasome activation, and a recombinant C-terminal domain could act directly on macrophage. The Prxs derived from E. histolytica triggered toll-like receptor 4-dependent activation of NLRP3 inflammasome in a cell/cell contact-independent manner. Through genetic, immunoblotting or pharmacological inhibition methods, NLRP3 inflammasome activation was induced through caspase-1-dependent canonical pathway. Our data suggest that E. histolytica Prxs had stable and durable cell/cell contact-independent effects on macrophages following abundantly secretion during invasion, and the C-terminal of Prx was responsible for activating NLRP3 inflammasome in macrophages. This new alternative pathway may represent a potential novel therapeutic approach for amoebiasis, a global threat to millions.